2007
DOI: 10.1515/znb-2007-1014
|View full text |Cite
|
Sign up to set email alerts
|

An Improved and Green Preparation of 3-(Alkylthio)propionic Acids

Abstract: An efficient, facile microwave-assisted synthesis has been developed for the preparation of unsymmetrical sulfide derivatives from 3-mercaptopropionic acid and a wide variety of alkyl, allyl or aryl chlorides or bromides. The synthesis performed in ethanol at 80 or 120 • C using sodium hydroxide as a base, selectively without an offensive smell, generates 3-(alkylthio)propionic acids in good yields. Effects of reaction components, temperature, and the heating technique on the formation of the product and side-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[15] During our studies, we observed that an increase in the reaction temperature clearly greater than 100 C significantly accelerated the condensation. Our experiences related to the synthetic applications of microwave activation [17] encouraged us to study the effect of microwaves on this condensation reaction. In addition, the use of the closed microwave vessel would also help avoid moisture.…”
Section: Resultsmentioning
confidence: 99%
“…[15] During our studies, we observed that an increase in the reaction temperature clearly greater than 100 C significantly accelerated the condensation. Our experiences related to the synthetic applications of microwave activation [17] encouraged us to study the effect of microwaves on this condensation reaction. In addition, the use of the closed microwave vessel would also help avoid moisture.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 3-(propylthio)propionic acid was carried out as described by Vaismaa et al (2007). The oxidation of 3-(propylthio)propionic acid to P3SP was carried out as follows.…”
Section: Synthesis Of 3-(propylsulfonyl)propionic Acid (P3sp)mentioning
confidence: 99%